Economics of Transiting to Renewable Energy in Morocco : A General Equilibrium Analysis - Timilsina, Govinda R. (World Bank, Washington, DC, 2014)
Morocco has set an ambitious target of supplying 42 percent of electricity through renewable sources, 14 percent each through hydro, wind, and solar, by 2020. To analyze the economic and environmental implications of implementing this target, this study uses a dynamic computable general equilibrium model with foresight that includes explicit representation of various electricity generation technologies. Two types of policy instruments, a production subsidy financed through fossil fuel taxation and a renewable energy mandate financed through increased electricity prices, have been considered to attract investment in renewable energy. The study shows that meeting the renewable target would achieve up to 15 percent reduction of national greenhouse gas emissions in 2020 compared with a situation in the absence of the target, or the baseline. However, meeting the target would decrease household consumption of goods and services, thereby worsening household welfare. The study also shows that the renewable production subsidy financed through fossil fuel taxation is superior to the mandate policy to meet the renewable energy target in Morocco, as the former would cause a lower loss in economic welfare and a larger reduction of greenhouse gas emissions than the latter.